PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN PERKALIAN BERBASIS ESD UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN SISWA SEKOLAH DASAR - Lathifah Qurrotu Ainii (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a multiplication board game learning media based on Education for Sustainable Development (ESD) to improve elementary students’ conceptual understanding of multiplication. The research employed the 4D development model (Define, Design, Develop, Disseminate) with a trial subject of 26 third-grade students at SDN Pasirsari 03. Expert validation was analyzed using CVI and CVR, both yielding a score of 1.00 (very valid). Practicality was measured through responses from teachers (95%) and students (97.31%), both falling into the very practical category. Effectiveness was analyzed through pretest and posttest, resulting in an average N-Gain of 0.82 (high category), and the Wilcoxon test showed a significant difference (p < 0.05). Interview results indicated that the media increased student engagement and meaningful conceptual understanding. The media also integrates SDG-related values through contextual problem cards. This study concludes that ESD-based media is effective, practical, and feasible for teaching multiplication in elementary schools.